Phase Formation Process in CdSe Thin Films - Ibrahimova, L.N.; Abdullayev, N.M.; Aliyev, M.E.; Garashova, G.A.; Aliyev, Y.I. (East European Journal of Physics, 2024)
In this work, thin films of cadmium selenide of difrent thicknesses were obtained by chemical deposition and the processes of phase formation in them were studied. Thin layers with a thickness of d = 150 – 500 nm were obtained. Structural studies were carried out using X-ray diffraction. The spectra obtained at room temperature were analyzed. The presence of structural features of the CdSe compound in thin layers has been established. After a thickness d = 400 nm, the process of phase formation begins. The observed atomic planes and Miller indices during the phase formation process are determined.